Proceedings of the 2021 DigitalFUTURES The 3rd International Conference on Computational Design and Robotic Fabrication (CDRF 2021) - Yuan, Philip F.; Chai, Hua; Yan, Chao; Leach, Neil (Springer Nature, 2022)
This open access book is a compilation of selected papers from 2021 DigitalFUTURES-The 3rd International Conference on Computational Design and Robotic Fabrication (CDRF 2021). The work focuses on novel techniques for computational design and robotic fabrication. The contents make valuable contributions to academic researchers, designers, and engineers in the industry. As well, readers encounter new ideas about understanding material intelligence in architecture.